Gambaran Pengalaman Mengatasi Dismenorea pada Remaja Putri - Wati, Angeli Silvia; Tampubolon, Masrina Munawarah; Utami, Sri (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduce: Dysmenorrhea is a common gynecological issue that causes discomfort for several days during the menstrual period in women. Experiences and strategies for managing dysmenorrhea vary among adolescents, as pain is a subjective experience that is often difficult to measure objectively. This study aims to explore the experiences of adolescent girls in managing dysmenorrhea in the Rejosari Health Center area. Method: This study uses a qualitative method with a descriptive phenomenological approach. The research participants are seven adolescent girls in the Rejosari Health Center area, selected through purposive sampling according to inclusion criteria. Data was collected through in-depth interviews guided by semi-structured interview guidelines and analyzed using thematic analysis by Colaizzi. Data collection was completed. Results: The findings and discussion present five main themes: 1) Relying on pain relief medication, 2) Pain management through positioning, massage, and traditional remedies, 3) Seeking further medical treatment at healthcare facilities, 4) Relying on support from close individuals, and 5) Belief in myths and normalizing dysmenorrhea. Conslusion: Dysmenorrhea significantly impacts the activities of adolescent girls. They manage it through pharmacological, non-pharmacological methods and sometimes require emergency treatment. Support from close individuals helps, though myths still influence them. Education and family support are essential to help adolescents effectively manage dysmenorrhea.